Raman studies in tetragonal structure PbTeO3. (July 2017) - Ma, Yan; Wang, Wendan; Liu, Qijun; Zhang, Linji; Lei, Li; Zhang, Leilei; Liu, Zhengtang
Abstract: Raman spectra of tetragonal phase PbTeO3 have been acquired from single-crystal sample synthesized by hydrothermal method. Theory calculations have been carried out to analyze the Raman spectra. Raman bands between 600 cm −1 and 800 cm −1 are attributed to the internal modes of Te-O bonds in TeO3 pyramid, while Raman bands between 136 cm −1 and 400 cm −1 are assigned to the external modes of TeO3 pyramid. The vibration corresponding to Raman frequencies below 119 cm −1 are consisted of Pb lattice modes and external modes of TeO3 . The effects of pressure on the Raman spectrum of PbTeO3 have been investigated up to 23 GPa. A splitting of 119 cm −1 peak was observed at 13.4 GPa, which may caused by the rotation of TeO3 pyramid instead of the phase transition. Highlights: Raman spectrum and the corresponding vibrational modes of tetragonal PbTeO3 have been investigated. An obviously splitting of 119 cm −1 Raman peak was observed at 13.4 GPa when PbTeO3 has been squeezed to 23 GPa. The softening of vibrational modes was observed when pressure up to 20 GPa.